Territorialização turística das pousadas da rota ecológica, litoral norte de Alagoas - Silva, Thassia Ramalho Perciano da (2016)
Tourism is a globalized activity that has the potential to change territories because when tourism develops in a place it interferes in a way or another with the culture, environment and preexisting economy, through a process that is known as tourism territorialisation. This study aims to understand the territorial changes that have been caused by a set of 13 pousadas that are located along a tract of the north littoral of the Alagoas state, which is locally known as Rota Ecológica. This area consists of less-densely urbanized beaches of the Passo de Camaragibe, São Miguel dos Milagres and Porto de Pedras municipalities where the above-mentioned alternative tourism pousadas are located. Alternative tourism offerings seek to establish synergist relationships with the local environment, culture and economy, usually providing singular or innovative tourist attractions. So, this form of tourism differs from those of mass tourism in that the latter is based on standardized offerings that attract large numbers of tourists by means of economic tourist packages. Mass tourism frequently causes a reorganization of the territory away from the local previous reality. While mass tourism is the prevalent form of tourism on the north littoral of the Alagoas‟ state, the pousadas in point, which are related to the concepts of charm hotels and routes, have emerged as a differential tourist offer in the region of the Rota Ecológica. This study employed a qualitative research approach and it used as data collection instruments open exploratory interviews, direct field observation, photographic survey, and semi-structured interviews which were conducted with long-standing residents of the three municipalities of the Rota Ecológica. The study relied on the perception of the local interviewers regarding the uses of the local territory, prior to the arrival of the pousadas and at the time of data collection (second semester of 2015 and first semester of 2016). Results indicate that the territorialisation of the Rota Ecológica by the pousadas comprises responsible practices of tourism development, including a significant preoccupation with the environment and some degree of involvement with local communities. However, the interviewers also identified negative aspects resulting from the construction and operation of the pousadas. The hypothesis that was developed as part of the study, that is, that the pousadas functioned as quasi-enclaves, was confirmed in that the pousadas combine typical resort characteristics with aspects that are part of alternative forms of tourism, as is the case of the so-called community-based tourism.